Contribution of different antiretroviral regimens containing zidovudine, lamivudine and ritonavir-boosted lopinavir on HIV viral load reduction during pregnancy - Sripan P. (2017)
© 2016 International Medical Press. Background: Antiretroviral (ARV) regimens used for the prevention of mother-to-child transmission of HIV have evolved over time. We evaluated the contribution of different ARV regimens on the reduction of the plasma HIV RNA viral load (VL) during pregnancy. Methods: A total of 1,833 VL measurements from ARVnaive pregnant women participating in perinatal prevention trials in Thailand were included. Women received either zidovudine (ZDV) monotherapy, ZDV plus lopinavir/ ritonavir (LPV/r), or ZDV plus lamivudine (3TC) plus LPV/r. VL time-course during pregnancy was described as a function of pretreatment VL and treatment duration using an Emax non-linear mixed-effect model. VL reduction and median time to achieve a VL < 50 copies/ml were estimated for each regimen. Results: Among 745 women, 279 (37%), 145 (20%) and 321 (43%) received ZDV monotherapy, ZDV+LPV/r and ZDV+3TC+LPV/r, respectively. The predicted VL reduction from baseline to delivery after a median of 10 weeks of treatment were 0.5, 2.7 and 2.9 log10 copies/ml with ZDV monotherapy, ZDV+LPV/r and ZDV+3TC+LPV/r, respectively. At delivery, 1%, 57% and 63% of women receiving ZDV monotherapy, ZDV+LPV/r or ZDV+3TC+LPV/r had a VL < 50 copies/ml. The addition of 3TC to ZDV+LPV/r reduced the time to achieve a VL < 50 copies/ml and the higher the pretreatment VL, the larger the effect 3TC had on reducing the time to VL < 50 copies/ml. Conclusions: The addition of 3TC to ZDV+LPV/r was associated with a slight further VL reduction but the time to reach a VL < 50 copies/ml was shorter. This beneicial effect of 3TC is crucial for prevention of motherto-child transmission in women who receive ARVs late and with high pretreatment VL.